Autosomal recessive congenital cataract is associated with a novel 4-bp splicing deletion mutation in a novel C10orf71 human gene - Chograni, M.; Alahdal, H. M.; Rejili, M. (Human genomics, 2023)
Congenital cataract is one of the most genetically heterogeneous ocular conditions with different genes involved in its etiology. Here, we describe the analysis of a new candidate gene of a congenital bilateral cataract associated with polymalformative syndrome, moderate global developmental delay, microcephaly, axial hypotonia, intrauterine growth restriction and facial dysmorphism for two affected siblings. Molecular analysis included exome sequencing and genome wide homozygosity mapping revealed a region of homozygosity shared by the two affected siblings at 10q11.23. The new C10orf71 gene was included in this interval and direct sequencing of this gene revealed an already described homozygous c. 2123T > G mutation (p. L708R) for the two affected subjects. Interestingly, we revealed in contrast a 4-bp deletion on the 3'-splicing acceptor site of intron 3-exon 4, namely defined as IVS3-5delGCAA. The C10Orf71 gene expression analysis using RT-PCR showed an expression pattern in different fetal organs and tissues as well as in leukocytes and confirmed that the IVS3-5delGCAA deletion of the C10orf71 gene is a splicing mutation responsible for the shortening of the C10orf71 protein in the two related patients. The C10orf71 gene has not been described to date as associated to the autosomal recessive phenotype.